2012
DOI: 10.5006/0546
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Prediction of Chemical Inhibition Performance for Erosion-Corrosion Conditions in Sweet Oil and Gas Production

Abstract: The effects of sand erosion on inhibitor performance have been examined in a flow loop using an impinging jet test cell and different techniques such as long-term weight loss (WL), linear polarization resistance (LPR), potentiodynamic polarization (PDYN), 3-D profilometry, and electrochemical impedance spectroscopy (EIS). Inhibition mechanisms and the relation between inhibitor concentration and corrosion penetration rate are described by the Flory-Huggins, Frumkin, Temkin, and Langmuir adsorption isotherms. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The highest E-C rates were obtained at an impacting angle of 45° in all ECAP passes. This result is consistent with the findings reported by the other previous studies [26]. It is reported that the maximum E-C rate were obtained with impact angle ranges from 30° to 50° for a range of materials such as pure iron, 304 stainless steel and aluminum [26][27][28][29].…”
Section: Effect Of Ecap On Erosion-corrosion At Different Impacting Asupporting
confidence: 93%
See 2 more Smart Citations
“…The highest E-C rates were obtained at an impacting angle of 45° in all ECAP passes. This result is consistent with the findings reported by the other previous studies [26]. It is reported that the maximum E-C rate were obtained with impact angle ranges from 30° to 50° for a range of materials such as pure iron, 304 stainless steel and aluminum [26][27][28][29].…”
Section: Effect Of Ecap On Erosion-corrosion At Different Impacting Asupporting
confidence: 93%
“…On the other hand, at 45 • the normal and tangential components of the impacting force are equal and the rate of material removal is maximized. In case of pure copper samples, it is found that the impact angle has the major effect on the erosion mechanism of solid particles [26]. Further studies are needed to understand and verify this point.…”
Section: Effect Of Ecap On Erosion-corrosion At Different Sand Concenmentioning
confidence: 98%
See 1 more Smart Citation
“…Essa abordagem multidisciplinar para a corrosão por CO 2 , ou seja, o conhecimento da relação entre fluxo e corrosão por CO 2 , é uma necessidade emergente para a indústria do petróleo e, embora, existam muitas pesquisas correlatas, [6][7][8] torna-se necessário buscar uma metodologia de pesquisa aplicada, que reúna os esforços da comunidade científica e contribua de forma significativa para o entendimento da corrosão por CO 2 em condições de fluxo.…”
Section: Introductionunclassified
“…), flow velocity, impact angle, slurry composition, tested material, and temperature [13,14]. Various methods, such as slurry pot [6,[15][16][17], flow loop [18][19][20][21], and jet impingement systems [22][23][24][25], have been used to investigate the E-C behavior of materials. In addition to experimental studies, analytical methods for studying E-C behavior are being rapidly developed [26].…”
Section: Introductionmentioning
confidence: 99%